Pengaruh Kuat Tekan dan Kuat Geser pada Sampel Dry Side of Optimum (Optimum Kering) dan Wet Side of Optimum (Optimum Basah) Tanah Organik - Setiawan, Ade; Iswan, Iswan; Setyanto, Setyanto (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
Organic soils causing many problems for the construction to be built on it, is generally caused bythe physical properties of organic soils that have a very high water content and low carryingcapacity, so that organic soils have less favorable properties for the construction of civil buildings.In this case, there should be a study of compressive strength and shear strength.This research wasconducted in the laboratory by making a sample of the results of a standard compaction, then thesample is done in Optimum condition Dry side of optimum and Wet side of optimum. On the DrySide Of Optimum process, sample was given a reduction of 10% of the optimum water content,while the Wet Side Of Optimum given the addition of 10% of the optimum water content, then thesample is done soaking for 4 days after compaction testing standards.The test results ofcompressive strength and shear strength shows a sample of soil behavior in an Optimumconditions better than the sample in Dry Side Of Optimum conditions and Wet Side Of Optimum.This is due to the pores of the soil Optimum conditions experienced stability and development ofthe soil is very minimum to occurs. Compressive strength and shear strength test is to measurehow strong soil receiving compressive strength and shear strength given to the soil separated fromthe grains.Keywords: Organic Soil, Dry Side Of Optimum, Wet Side Of Optimum, Optimum, CompressiveStrength and Shear Strength